Adjuvant chemotherapy improves survival in high-risk stage II colon cancer: a retrospective cohort study. (November 2022) - Liu, Lin-Lin; Xiang, Zuo-Lin
Background: The survival advantage of postoperative chemotherapy for high-risk stage II colon cancer (CC) patients remains unclear. Objectives: The purpose was to evaluate the survival of high-risk stage II CC cases treated with chemotherapy and to construct survival prediction models to predict the survival benefit from chemotherapy. Design: The study is a retrospective observational cohort study. Methods: Data on patients with stage II CC diagnosed from 2005 to 2019 who underwent radical surgery were obtained from the Surveillance, Epidemiology and End Results (SEER) database. A 1:1 propensity score matching (PSM) was applied to obtain two cohorts, chemotherapy versus no chemotherapy. A chi-square analysis was used to assess the differences before and after PSM in the above two groups. Kaplan–Meier survival analysis and Cox proportional hazards regression were applied to investigate the 5- and 10-year overall survival (OS) and cancer cause-specific survival (CSS). The predictive power of the constructed models was assessed by the concordance index (C-index) and calibration curves. Results: Of the 37, 050 cases, 14, 744 (39.8%) stage II CC were at high-risk and 29.2% of them received chemotherapy. Age, T stage, marital status, histologic grade, gender, and site independently influenced the reception of chemotherapy. The survival advantage of chemotherapy in the high-risk patients remained positive before and after PSM. The estimated 3, 5, and 10 years OS rates of chemotherapy group were 9.3, 10.7, and 15.6% higher than the nonchemotherapy group, respectively. Four nomograms predicting OS and CSS were established, with great discrimination (C-index between 0.627 and 0.691) and excellent calibration. Conclusion: Postoperative chemotherapy is beneficial for high-risk stage II CC patients, including the elderly patients (over 65 years of age). Our study developed nomograms to quantify the survival benefit of chemotherapy among high-risk stage II CC patients to develop personalized treatment recommendations and guide management decisions.